Delayed diagnosed atypical case of Andersen-Tawil syndrome - Ahmet Z. Burakgazi (MDPI AG, 2019)
Andersen-Tawil syndrome (ATS) is characterized by a triad of periodic paralysis, cardiac arrhythmias and distinctive dysmorphic features. Due to its rarity and high degree of clinical and phenotypic variability, a diagnosis of ATS can be very perplexing and challenging. Herein, an atypical case of ATS with a complicated presentation that caused an approximately 11-year delay in diagnosis is reported. The patient made a full recovery with acetazolamide after the diagnosis. The case and its management are presented with an updated literature review.